Arterial Thromboembolism in a patient with Ischemic Dilated Cradiomypathy (IDCM) - Islam, Md Saiful; Hossain, Md Alamgir; Talukder, Ranjan; Moniruzzaman, Md (KYAMC Journal, 2013)
Mrs. Shikha, 51 years old pleasant lady presented to us with the complaints of acute severe pain in the left leg associated with bluish discoloration for 5 days. She is a known case of Ischemic Dilated cardiomyopathy (IDCM) for last 6 years & had history of formation of LV thrombus for repeated times. She was on regular anti-platelets, anti-ischemic & anti-coagulant drugs. Recently her echocardiogram report revealed- IDCM, Mitral regurgitation (gr-11), spontaneous echo contrast within LV, LVEF- 24%. On this admission her CT coronary angiogram of lower limb vessels revealed total occlusion associated with thrombosis of left common iliac, external iliac & internal iliac, distal popliteal, ant. & post. tibial, peroneal arteries, & on right side diffuse atherosclerosis of distal popliteal, ant & post tibial arteries. Patient was treated with anticoagulants, anti platelet, anti-ischemic & other relevant medications & referred to vascular surgeon. DOI: http://dx.doi.org/10.3329/kyamcj.v2i1.13521 KYAMC Journal Vol.2(1) 2011 pp.149-151